Hebrews : a new translation with introduction and commentary - Koester, Craig R.; Koester, Craig R., 1953- (New Haven : The Anchor Yale Bible, 2001)
"One of early Christianity's most carefully crafted sermons, Hebrews addresses listeners who have experienced the elation of conversion and the heat of hostility, but who now must confront the formidable task of remaining faithful in a society that rejects their commitments. The letter probes one of the most profound question of faith: If it is God's will that believers be crowned with glory and honor, why are the faithful subject to suffering and shame?
Through the stories of Abraham and Sarah, Moses, and Rahab, whose faith enabled them to overcome severe trials and conflicts, and through the story of Jesus himself, whose sufferings opened the way to God's presence for all, the sermon confirms the foundations of the Christian faith."--BOOK JACKET.
Hebrews: A Translation. I. History of Interpretation and Influence. II. Social Setting. III. Formal and Rhetorical Aspects. IV. Selected Issues in the Theology of Hebrews. V. Text of Hebrews -- Translation, Notes, And Comments. I. Exordium. II. Proposition. III. Arguments. IV. Peroration. V. Epistolary Postscript. Contributors to The Anchor Bible.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Hebrews -- Commentaries